Selection of Yeasts for Breadmaking by the Frozen-Dough Method - Oda, Yuji (1986)
Eleven yeast strains suitable for frozen dough were selected from over 300 Saccharomyces strains. All of these were identified as Saccharomyces cerevisiae from morphological, cultural, and physiological characteristics. The selected yeast cells accumulated a higher amount of trehalose than did commercial bakers' yeast cells.